Sovremennye predstavleniya o fiziologicheskikh mekhanizmakh srochnoj adaptatsii organizma sportsmenov k vozdejstviyam fizicheskikh nagruzok - Vysochin, Ju. V.; Denisenko, Ju. P. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The problem of adaptation to physical overloads in extreme conditions of sports activity concerns to number of the most actual problems of the modern sports physiology and medicine. The existence of the relaxation mechanism of the urgent adaptation was revealed during the long-term researches. The name of the relaxation mechanism of urgent mobilization of protection (RMUP) of an organism from the extreme influences was given to it. It was experimentally proved, that the activization of the RMUP provides occurrence of the effect of the emergency increase of the serviceability. The further researches have shown, that the RMUP predetermines the general efficiency, the level of physical serviceability and the stability to the extreme influences and it can be related to the category of functional systems under the name of nonspecific "breaking relaxation functional system of urgent adaptation and protection" of an organism from the extreme influences. Its main working principle is the economization of the power expenses. And as the main components, the brake systems of central nervous system and relaxation mechanisms of nervous-muscular system.